2019
DOI: 10.21037/atm.2019.06.08
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors related to microvascular complications in patients with type 2 diabetes mellitus in Tianjin, China: a cross-sectional study

Abstract: Background: Since chronic hyperglycemia-related damage to small blood vessels results in complications, patients with longer durations of type 2 diabetes mellitus (T2DM) are more likely to develop microvascular complications, such as retinopathy, neuropathy and nephropathy, which are very harmful to the health of humans. Therefore, this study aimed to assess the prevalence of diabetes-related microvascular complications and to explore their risk factors in patients with T2DM in Tianjin, China.Methods: This obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 21 publications
5
24
1
2
Order By: Relevance
“…Type 2 diabetes mellitus (T2DM) is a type of progressive endocrine disease associated with various metabolic disorders that is clinically characterized by hyperglycemia. 1 According to the latest Diabetes Atlas released by the International Diabetes Federation (IDF) in 2019, approximately 463 million adults aged 20 to 79 years old in the world have diabetes. It is estimated that in 2045, the number of individuals with diabetes mellitus (DM) will reach 700.2 million.…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) is a type of progressive endocrine disease associated with various metabolic disorders that is clinically characterized by hyperglycemia. 1 According to the latest Diabetes Atlas released by the International Diabetes Federation (IDF) in 2019, approximately 463 million adults aged 20 to 79 years old in the world have diabetes. It is estimated that in 2045, the number of individuals with diabetes mellitus (DM) will reach 700.2 million.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a progressive disease accompanied by metabolic disorders and microvascular complications such as retinopathy, neuropathy, and nephropathy. [1][2][3][4] Diabetic retinopathy (DR) is considered one of the most common and severe complications of DM and a major cause of blindness worldwide. Also, it is associated with loss of productivity and quality of life, and may lead to additional socioeconomic burden.…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathy is most common which is followed by nephropathy and retinopathy least among all. This is supported by the work of Kosiborod M, Gomes MB et al 18,19 Bui HDT, Jing X, has reported that neuropathy is most common complication, but retinopathy comes second. But Agrawal RP et al, has concluded retinopathy and nephropathy were the commonest complications of diabetes which does not support our study.…”
Section: Resultsmentioning
confidence: 68%